TELAAH ILMU MUKHTALIF PADA HADIS KONTRADIKTIF - Zunda Zubaidah, Nur; Umar, Athoillah (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2023)
The position of hadith as a source of Islamic law is something that we must pay attention to. The function of hadith to the Qur'an is as bayan taqrir, bayan tafsir, and bayan tasyri'. However, not all hadith have the same intent and meaning. After much research, several hadith were found whose meanings seem to contradict each other. This triggered the determination of some scholars to find a suitable resolution to the conflicting hadith. The study of hadith science has a branch that deals with seemingly contradictory traditions, namely the science of mukhtalif hadis. In line with the times and scientific development, the study of mukhtalif science has become something that is commonly studied in various scientific institutions. Some of the scholars' methods of resolution and their application to contradictory hadith are being called for again. This article will be devoted to the application of the method of resolution to the muchtalif traditions on the prohibition and permissibility of relieving oneself facing the Qibla. There are two traditions reported in Imam Malik's Muwatta' index number 2 and Sunan al-Baihaqi's index number 442 that speak of the prohibition and permissibility of relieving oneself. Judging from their meanings, it is known that the two traditions appear to be contradictory and this article will explain the resolution of the two traditions.